On Promoting Fiscal Discipline : The Role of Exchange Rate Regimes, Fiscal Rules and Institutions - Keita, Kady; Turcu, Camelia (World Bank, Washington, DC, 2019)
This paper examines how fiscal rules, exchange rate regimes, and institutional quality affect the cyclical behavior of fiscal policy (how government spending responds to fluctuations in gross domestic product). The analysis is performed on a panel of 153 advanced, emerging, and developing countries over 1993-2015 using local Gaussian-weighted ordinary least squares and two-stage least squares estimators. The findings show that the adoption of fiscal rules alone is not sufficient to promote countercyclical fiscal policy and should be combined with strong institutions. Moreover, fiscal rules seem to limit procyclicality, especially in countries with flexible exchange rate regimes rather than in countries with fixed exchange rates. The analysis also finds that the disciplining effect of fiscal rules depends on the type of rule.